Greenhouse solar drying of tarragon: Mathematical modeling and quality features - Mohammad Noshad; Morteza Taki; Parisa Ghasemi; Mitra Payan Gandomani (Journal of Agriculture and Food Research)
The purpose of this study was to evaluate the effectiveness of a Greenhouse Solar Dryer (GSD) in drying tarragon leaves and contrast it with common drying methods. The study selected the 11 best mathematical models from the literature to qualify the drying kinetics of tarragon leaves. The results showed that the average exposure time in the GSD method was 3.6 and 4.6 times less than exposure in direct sunlight and in the shade, respectively. The Wang and Singh model with R2 = 0.9968, RMSE = 0.0181 and χ2 = 0.0016 was identified as the best model for GSD. The diffusion model with R2, χ2 and RMSE of 0.9847, 0.9520, 0.0008, 0.0020, 0.0327 and 0.0575, respectively, was identified as the best model for sun exposure and in the Shade. The color change of dried tarragon, expressed as the total change index (ΔE), was recorded as 10.9 ± 0.1 in shade, 12.9 ± 0.2 in GSD and 16.8 ± 0.1 in sun exposure. The average amount of dry tarragon essential oil extracted by hydro-distillation was 1.6 ± 0.1, 1.8 ± 0.1 and 0.95 ± 0.07 (mL/100 g) for shade, GSD and sun exposure, respectively. The results showed that using GSD and shade exposure increased the TPC in the samples, while sun exposure decreased the TPC compared to the raw samples. The greenhouse solar-dried sample showed the highest DPPH scavenging activity at 85 ± 1 %, which was in line with the TPC results. Following closely was the shade-dried sample at 81 ± 1 %. The sun-dried sample exhibited the lowest activity at 56 ± 1 %. In general, GSD drying is suggested as an eco-friendly technique that can be used to dry tarragon, which can then be utilized as a valuable source of bioactive compounds in the food and pharmaceutical industries.